2007
DOI: 10.2135/cropsci2006.12.0780
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal and Longitudinal Adaptation of Switchgrass Populations

Abstract: Switchgrass (Panicum virgatum L.) is a warm‐season native grass, used for livestock feed, bioenergy, soil and wildlife conservation, and prairie restoration in a large portion of the USA. The objective of this research was to quantify the relative importance of latitude and longitude for adaptation and agronomic performance of a diverse group of switchgrass populations. Six populations, chosen to represent remnant prairie populations on two north–south transects, were evaluated for agronomic traits at 12 locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
215
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(233 citation statements)
references
References 44 publications
17
215
0
1
Order By: Relevance
“…Flowering time and photoperiod response are probably the most important traits regulating adaptive variation in switchgrass. For most cultivars, adaptation and productivity decrease significantly when the cultivar is grown in more than one hardiness zone north or south of its origin (Casler et al 2004(Casler et al , 2007b. More recent applications of DNA markers and sequencing methodologies have suggested that both cpDNA sequence data and nuclear DNA markers are highly correlated with the upland and lowland phenotypic classes.…”
Section: Geographic Distribution Of Ecotypes and Lineagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Flowering time and photoperiod response are probably the most important traits regulating adaptive variation in switchgrass. For most cultivars, adaptation and productivity decrease significantly when the cultivar is grown in more than one hardiness zone north or south of its origin (Casler et al 2004(Casler et al , 2007b. More recent applications of DNA markers and sequencing methodologies have suggested that both cpDNA sequence data and nuclear DNA markers are highly correlated with the upland and lowland phenotypic classes.…”
Section: Geographic Distribution Of Ecotypes and Lineagesmentioning
confidence: 99%
“…Mutations that resulted in earlier flowering and tolerance to longer daylength, allowed certain genotypes to complete cold-hardening cycles and produce ripe seed at more northern latitudes. Divergence in flowering time and photoperiod sensitivity is the basis for much of the phenotypic variability observed within the species today (Casler et al 2007b). The vast majority of phenotypic variability in switchgrass occurs along latitudinal gradients, with earlier flowering, fewer phytomers, greater tiller density, reduced tiller size, and more compact panicle structure associated with more northern origins (Casler et al 2004(Casler et al , 2007b.…”
Section: Geographic Distribution Of Ecotypes and Lineagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrolyte leakage was lowest in "Dakota" compared with all other grasses tested, and CIR was close to the highest [214]. Lowland cytotypes are particularly susceptible to cold winter conditions, as they are adapted to southern latitudes [222,223]. Panicum virgatum shows unusual tolerance to cold night temps for a C 4 grass [224].…”
Section: C4mentioning
confidence: 99%
“…Panicum virgatum C4 Moderate Lowland cytotypes of Panicum virgatum, adapted to southern climates, may be more heat tolerant than upland types [223]. Even though plant height and total biomass decreased under heat stress [249], a climate modeling paper shows that Panicum virgatum yields could increase under warmer climate scenarios (3 to 8°C), due to extended growing season and limited cold stress [211].…”
Section: Cam Highmentioning
confidence: 99%